Are Congregations Texts? (Homiletic, 2014)
It is a common sentiment among homileticians that preaching requires exegeting both the scriptural text and the congregational context. The relevancy of the preaching message, it is argued, depends in part upon a deep knowledge of the congregational culture. The preacher is therefore encouraged to “read” the culture of the congregation and discern how the symbols, practices, and actions of the congregation are used to make meaning so that the preacher might construct a fitting sermon. In this way, the congregation is likened to a text that awaits a reading by a literate observer. In this paper, I examine the limitations of such an analogy arguing that while a semiotic approach to congregations has merit it is often blind to the ways in which power and production influence the creation and reproduction of the congregational culture. Finally, the paper concludes with descriptions from recent homiletical works that offer productive alternatives to the semiotic approach to congregational study.